FROM NOTHING TO BE A THING BY WASTE BANK MANAGEMENT - Ahmadi, Rulam; Suprihandari, Miya Dewi; Wulansari, Dyah; Kurniawati, Yuli; ., Mahmudah (2021)
Waste has been a part of human life since the beginning of civilization. Waste is the end result of activities carried out by humans and nature that are wasted and do not have economic value. Waste problems mainly occur in urban areas because of high population density and activity and are problems that are difficult to overcome and require proper handling. Conventional waste handling by collecting, transporting and disposing to landfills (TPS) has not been able to solve the waste problem completely, therefore innovation is needed in handling and processing waste as a whole so that it has a positive impact on the health of the environment and the economy of the community. One of the innovations or alternative solutions in handling waste is through community empowerment, namely by forming a waste bank. The program is integrating the principles of 3R in waste management (Reduce, Reuse, Recycle) will make community empowerment more effective and efficient by creating creative ideas in processing waste. The government of Surabaya, as one of the second largest cities in Indonesia with a high population density has quite complex waste problems. Several programs have been carried out to deal with the waste problem, including through community empowerment by involving government participation. Here, we use a qualitative descriptive method that aims to convey facts about waste management by empowering the community and the impact of implementing the program both from an economic and environmental standpoint, especially in the Surabaya area. The research shows that changing something from zero value things requires high collaboration and creativity which is shown by the handling of waste through a waste bank program with creative ideas of the community and the participation of the government that have had a positive impact, for everyone, environment and nation in the future. Keywords: Waste, Waste Bank, Community Empowerment